2017
DOI: 10.4103/ijo.ijo_407_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of amniotic membrane and full-thickness skin graft in reconstruction of kissing nevus of eyelids

Abstract: A 20-year-old girl presented with a large pigmented lesion over the temporal aspect of left lateral canthus involving the lateral one-third of both eyelids, since birth. A slow increase in its size had been noticed for the past 2 years. On examination, a hairy nevus measuring 34 mm × 22 mm was noticed involving left eyelid skin, the mucocutaneous junction (MCJ), palpebral conjunctiva, and lateral canthus. The surface was irregularly thick and covered with long, thick, and pigmented hairs. A clinical diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Various grafts have been used, including cryopreserved, ultra-thick, fresh, and dehydrated amniotic membrane. 13,[57][58][59][60][61][62][63][64] Mainly, case reports and case series have been published. Patient populations have included those with conjunctival melanoma with eyelid involvement, orbital sebaceous carcinoma involving the lower eyelid, squamous cell and basal cell carcinoma, and superficial lower eyelid defects after Mohs surgery.…”
Section: Reconstruction After Palpebral or Forniceal Conjunctival Les...mentioning
confidence: 99%
See 1 more Smart Citation
“…Various grafts have been used, including cryopreserved, ultra-thick, fresh, and dehydrated amniotic membrane. 13,[57][58][59][60][61][62][63][64] Mainly, case reports and case series have been published. Patient populations have included those with conjunctival melanoma with eyelid involvement, orbital sebaceous carcinoma involving the lower eyelid, squamous cell and basal cell carcinoma, and superficial lower eyelid defects after Mohs surgery.…”
Section: Reconstruction After Palpebral or Forniceal Conjunctival Les...mentioning
confidence: 99%
“…Patient populations have included those with conjunctival melanoma with eyelid involvement, orbital sebaceous carcinoma involving the lower eyelid, squamous cell and basal cell carcinoma, and superficial lower eyelid defects after Mohs surgery. 13,[56][57][58][59][60][61][62][63][64] One case series describes the use of dehydrated amniotic membrane placed over superficial defects of the lower eyelid after Mohs surgery measuring up to 2.5 × 1.5 cm and reported successful healing in 3 patients without surgical reconstruction. 63 All three cases had a minimal extension of the Mohs defect into the orbicularis oculi.…”
Section: Reconstruction After Palpebral or Forniceal Conjunctival Les...mentioning
confidence: 99%
“…While the majority of AMGs are used in anterior segment surgeries, more recent studies have reported on AMG use in eyelid reconstruction procedures 7 as well as the recreation of the mucocutaneous junction along with full-thickness skin grafts for epithelial growth. 8 AMGs are also commonly utilized in the treatment of severe inflammatory conditions such as Stevens–Johnson Syndrome/Toxic Epidermal Necrolysis (SJS/TENs). AMGs have proven to be an acceptable alternative to autologous grafts because of its ease-of-use and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%